Pengaruh Brand Image, Influencer Marketing, dan Kualitas Produk terhadap Keputusan Pembelian Gen Z pada Produk Erigo - Indah Rizqi Tsania; Misti Hariasih; Rizky Eka Febriansah (Ekonomis: Journal of Economics and Business, 2026)
This study aims to examine the impact of Brand Image, Influencer Marketing, and Product Quality on Gen Z Purchasing Decisions on Erigo products. This study uses a quantitative and survey approach. Sampling uses a non-probability sampling technique and the research sample is Gen Z in Sidoarjo Regency who have purchased Erigo products, with a sample size of 100 respondents. Data collection through an online questionnaire sent via Google Form. Indicator measurements apply a Likert scale and are analyzed using SmartPLS 4.0 through validity, reliability, R-Square testing, and hypothesis testing. The results of the study revealed that there is a significant influence between the variables of brand image, influencer marketing, and product quality on Gen Z purchasing decisions on Erigo products. This finding confirms that the strength of brand image, influencer credibility, and consistency of product quality play a major role in increasing Gen Z's interest and purchasing decisions towards local products such as Erigo.